PEMUPUKAN NPK MAJEMUK PADA BIBIT JABON MERAH (Anthocephalus macrophyllus (Roxb.) Havil) - Luhulima, F. S.; Lasut, M. T.; Kainde, R. P.; Thomas, A. (EUGENIA, 2017)
ABSTRACT Various doses of NPK fertilization  could increase plant growth. This research studied  the effect of NPK compound fertilizer with some kind of dose on the growth of seedlings of red jabon. This research was conducted at the Laboratory of Silviculture Faculty of Agriculture, University of Sam  Rarulangi which lasted from May until June 2012, The objectives of this study were to determine the effect of compound NPK fertilizers on the growth of seedlings of red jabon. The research used experimental design of Randomized Block Design (RBD), Each treatment was replicated 5 times and each replication consisted of 5 red jabon seedlings. The treatments being given were: (1) without fertilizer (control), (2) 1 g of NPK/ plant, (3) 2 g of NPK/plant, (4)  3 g of NPK/plant and (5) 4 g of NPK/plant.  The results of this research showed that compound fertilizer NPK influence to high growth, diameter,  number of leaves, root volume and dry weight of seedlings red jabon canopy. NPK fertilizer with a dose of 3 g/plant  (D) can increase height growth,  diameter and number of leaves. While the parameters of the root volume and dry weight of the canopy, NPK treatment media with 4 g/plant (E) gives better results.Keywords : NPK fertilization, growth seedling, red jabon ABSTRAK Pemupukan NPK dengan berbagai dosis dapat meningkatkan pertumbuhan tanaman. Dalam penelitian ini dipelajari pengaruh pemupukan majemuk NPK dengan beberapa macam dosis terhadap pertumbuhan bibit jabon merah. Penelitian ini dilaksanakan di Laboratorium Silvikultur Fakultas Pertanian Universitas Sam Rarulangi yang berlangsung mulai Mei s/d Juni 2012. Tujuan dari penelitian ini ialah untuk mengetahui pengaruh pemupukan majemuk NPK terhadap pertumbuhan bibit jabon merah. Penelitian ini menggunakan metode eksperimen Rancangan Acak Kelompok (RAK), setiap perlakuan diulang sebanyak 5 kali dan setiap ulangan terdiri atas 6 bibit jabon. Perlakuan yang diberikan adalah : (1) tanpa pupuk (kontrol), (2) pupuk NPK 1 gram/tanaman, (3) pupuk NPK 2 gram/tanaman, (4) pupuk NPK 3 gram/tanaman dan (5) pupuk NPK 4 gram/tanaman. Hasil penelitian menunjukkan bahwa terdapat pengaruh dosis pupuk majemuk NPK terhadap pertumbuhan tinggi, diameter, jumlah daun, volume akar dan berat kering tajuk bibit jabon merah. Pemupukan NPK dengan dosis 3 gram/tanaman (D)  dapat meningkatkan pertumbuhan tinggi, diameter dan jumlah daun. Sedangkan pada parameter volume akar dan berat kering tajuk, media dengan perlakuan NPK 4 gram/tanaman (E) memberikan hasil yang lebih baik.Kata kunci :  pemupukan NPK, pertumbuhan bibit, jabon merah